The many adventures of Winnie the Pooh - Holloway, Sterling; Winchell, Paul; Cabot, Sebastian (Distributed by Buena Vista Home Entertainment, 2002)
These charming stories are filled with timeless Pooh adventures-- the first meeting between Tigger and Pooh, Pooh getting stuck in Rabbit's house from eating too much honey, and the lovable characters' flurry of activity on a hilarious windy day